Causes of paroxysmal dyspnea in patients with stable coronary artery disease - S. F. Yarmedova; I. S. Yavelov; O. M. Drapkina (Столичная издательская компания, 2024)
Aim. To study possible causes of dyspnea in patients with stable coronary artery disease (CAD).Material and methods. 101 patients with stable CAD and paroxysmal dyspnea who underwent inpatient treatment in the cardiology department were included in the observational study. The following parameters were analyzed: presence and severity of dyspnea, angina pectoris, chronic heart failure (CHF), anxiety and/or depression, results of physical examination, electrocardiography,laboratory tests (levels of high sensitive cardiac troponin, natriuretic peptide and thyroid-s timulating hormone in the blood), a 6 minute walk test, multispiral computed tomography or chest X-ray, Holter monitorechocardiography, stress echocardiography with a treadmill load, spirometry with a bronchodilation test, as well as coronary angiography, which was performed in the detection of myocardial ischemia were.Results. Transient myocardial ischemia as a cause of dyspnea was diagnosed in 36 patients (35.6%). At the same time, chest pain during stress echocardiography was noted only in 5% of cases. In addition to myocardial ischemia, the following possible causes of dyspnea were found: CHF with preserved left ventricular ejection fraction (EF) in 76 patients (75.2%), obesity - in 34 (33.7%), anxiety - in 33 (32.7%), valvular pathology - in 28 (27.7%), pulmonary ventilation disorders - in 21 (20.8%), depression - in 20 (19.9%), cardiac rhythm and conduction disorders - in 9 (8,9%), thyroid dysfunction - in 7 (6.9%), CHF with mildly reduced EF - in 7 (6.9%), CHF with reduced EF - in 2 (2.0%), anaemia - in 2 (2.0%). The potential cause of dyspnea was not established in 2 patients (2.0%). One cause of dyspnea was diagnosed in 8.9%, a combination of two causes - in 38.6%, three - in 25.7%, four - in 15.8%, five - in 6.9%, six causes - in 1% of participants. Dyspnea commonly was associated with transient myocardial ischemia combined with CHF with preserved EF (17%), as well as CHF with preserved EF and valvular pathology (13.9%).Conclusion. The obtained results confirm the variety of possible causes of dyspnea in patients with stable CAD, as well as the fact that transient myocardial ischemia is not the most common cause of dyspnea in this category of patients and in many cases is combined with other disorders accompanied by similar symptoms.